Qualitative study of participants' perceptions and preferences regarding research dissemination. Issue 2 (3rd April 2017) - Purvis, Rachel S.; Abraham, Traci H.; Long, Christopher R.; Stewart, M. Kathryn; Warmack, T. Scott; McElfish, Pearl Anna
ABSTRACT: Background : The study identifies the experiences, preferences, and perceptions of research participants regarding dissemination of research findings at the participant level and community level.Methods : The qualitative study utilized focus-group methodology to explore research participants' experiences and preferences for the dissemination of research findings. Five focus groups were held with 53 participants who were recruited through existing community advisory boards in Arkansas.Results : Participants stated that researchers should always offer to share research findings. Participants explained that disseminating findings is appropriate because of their sense of ownership of results, it encourages participation facilitating higher quality research, and it may foster greater trust between researchers and participants. Participants also provided insights on how research findings should be shared, including recommendations for appropriate mode, timing, and context, as well as ways to share sensitive findings and the role of community partners in dissemination.Conclusions : This study is consistent with other studies that document participants' desire to receive research findings and expands our knowledge by documenting participants' rationale for why they think it is important and their recommendations for how to share results. Further research is needed to understand why researchers are not disseminating study findings to participants and to test the best ways to share results.